The Nablus 1968 hoard - Gitler, Haim. (New York)
209 sayfa, xli sayfa resim
Keywords: “The Nablus 1968 Hoard is the largest late Persian/early Hellenistic period coin and jewelry hoard recorded from the southern Levant and the largest known hoarded assemblage of Samarian coins. This study provides a detailed catalogue of all the coins and pieces of jewelry the authors managed to record“ --